C42 MULTI–CHAMBER SPECKLE TRACKING IMAGING AND DIAGNOSTIC VALUE OF LEFT ATRIAL STRAIN IN CARDIAC AMYLOIDOSIS. (18th May 2022) - Aimo, A; Fabiani, I; Giannoni, A; Mandoli, G; Pastore, M; Vergaro, G; Spini, V; Chubuchny, V; Pasanisi, E; Petersen, C; Poggianti, E; Taddei, C; et al.
Abstract: Background: Amyloid deposits in all cardiac chambers, impairing their function. We investigated for the first time if a speckle–tracking echocardiography (STE) analysis extended to all 4 chambers might hold additive diagnostic value for CA and its subtypes (amyloid transthyretin [ATTR–] and light–chain [AL]–CA). Methods: We evaluated 423 consecutive patients undergoing a diagnostic workup for CA in 2 referral centres from 2015 to 2020. Results: CA was diagnosed in 261 patients (62%; ATTR–CA, n = 144, 34%; AL–CA, n = 117, 28%). Patients with CA had an impaired function of all cardiac chambers, particularly those with ATTR–CA. Peak left atrial longitudinal strain (LA–PALS) was the only STE parameter that predicted CA and ATTR–CA independent of laboratory and standard echocardiographic variables (Model 1). It also predicted ATTR–CA among patients with unexplained hypertrophy regardless of a diagnostic score (IWT score). Patients with either LA–PALS or LA–peak atrial contraction strain (PACS) in the first quartile (LA–PALS <6.65% or LA–PACS <3.62%) had an almost 4–fold higher likelihood of CA and ATTR–CA regardless of Model 1. Among patients with unexplained hypertrophy, those with LA–PALS or LA–PACS in the first quartile had an almost 9–fold higher likelihood of ATTR–CA irrespective of Model 1, and a 2–fold higher likelihood of ATTR–CA beyond the IWT score. Conclusions: STE measures of all 4 chambers are abnormal in patients with CA, particularly in those with ATTR–CA. LA strain holds independent diagnostic significance. Among patients screened for CA, those with LA–PALS <6.65% and/or LA–PACS <3.62% have a high likelihood of CA and ATTR–CA.